Gravity-regulated localization of PsPIN1 is important for polar auxin transport in etiolated pea seedlings: Relevance to the International Space Station experiment. (August 2019) - Kamada, Motoshi; Oka, Mariko; Inoue, Riko; Fujitaka, Yayoi; Miyamoto, Kensuke; Uheda, Eiji; Yamazaki, Chiaki; Shimazu, Toru; Sano, Hiromi; Kasahara, Haruo; Suzuki, Tomomi; Higashibata, Akira; et al.
Abstract: To clarify the mechanism of gravity-controlled polar auxin transport, we conducted the International Space Station (ISS) experiment "Auxin Transport" (identified by NASA's operation nomenclature) in 2016 and 2017, focusing on the expression of genes related to auxin efflux carrier protein PsPIN1 and its localization in the hook and epicotyl cells of etiolated Alaska pea seedlings grown for three days in the dark under microgravity (μ g ) and artificial 1  g conditions on a centrifuge in the Cell Biology Experiment Facility (CBEF) in the ISS, and under 1  g conditions on Earth. Regardless of gravity conditions, the accumulation of PsPIN1 mRNA in the proximal side of epicotyls of the seedlings was not different, but tended to be slightly higher as compared with that in the distal side. 2, 3, 5-Triiodobenzoic acid (TIBA) also did not affect the accumulation of PsPIN1 mRNA in the proximal and distal sides of epicotyls. However, in the apical hook region, TIBA increased the accumulation of PsPIN1 mRNA under μ g conditions as compared with that under artificial 1  g conditions in the ISS. The accumulation of PsPIN1 proteins in epicotyls determined by western blotting was almost parallel to that of mRNA of PsPIN1 . Immunohistochemical analysis with a specific polyclonal antibody of PsPIN1 revealed that a majority of PsPIN1 in the apical hook and subapical regions of the seedlings grown under artificial 1  g conditions in the ISS localized in the basal side (rootward) of the plasma membrane of the endodermal tissues. Conversely, in the seedlings grown under μ g conditions, localization of PsPIN1 was greatly disarrayed. TIBA substantially altered the cellular localization pattern of PsPIN1, especially under μ g conditions. These results strongly suggest that the mechanisms by which gravity controls polar auxin transport are more likely to be due to the membrane localization of PsPIN1. This physiologically valuable report describes a close relationship between gravity-controlled polar auxin transport and the localization of auxin efflux carrier PsPIN1 in etiolated pea seedlings based on the μ g experiment conducted in space.